Asymmetry and helplessness: the copyright ecology of online literature writers in China*. Issue 4 (November 2018) - Wang, Zhigang; Wing, Mark
Abstract : The gradual increase in the output of China's online literature industry and strengthening of the copyright development chain has yet to result in any standardization of copyright management. This article provides an analysis of discrimination against online literature writers, as their writing is usually considered less creative than conventionally published work. This paper then analyses the rampant piracy and plagiarism plaguing online literature in China and the difficulty authors encounter in protecting their rights. After examining this environment, the article discusses the reasons behind the dysfunctional copyright ecology facing online literature writers. It focuses on the position of the online literature platform, namely the potential capital advantage of the platform and associated weakening of the 'elite' label applied to certain online literature writers following from the freemium business model. Unclear management from the government is also addressed.